Characteristics, course and condition of patients presenting to an adolescent medicine eating disorder program: A three-year study - Sona Dave; Ronald Feinstein; Nadia Saldanha; Eric Weiselberg; Linda Carmine; Martin Fisher (Global Pediatrics, 2023)
Purpose: Evaluate clinical characteristics at initiation, during, and at discontinuation of care for patients with eating disorders regardless of reason for discontinuation of care. Methods: A chart review of 279 patients who presented to the Division of Adolescent Medicine of Cohen Children's Medical Center (Northwell Health, New York) between May 1, 2014 and April 30, 2015. Demographics and clinical information including anthropometry, last menstrual period (LMP), caloric intake, eating disorder behaviors, length of illness, DSM-5 eating disorder diagnosis was collected from 2734 visits. Results: 45% of patients had Anorexia Nervosa (AN), 24% had Atypical Anorexia Nervosa (AAN), 15% had Bulimia Nervosa/Purging Disorder (BN/PD), and 17% had Avoidant Restrictive Food Intake Disorder (ARFID). Patients on average were sick for 18 months and lost 20 pounds prior to presentation. Physicians indicated they wanted patients to remain in active treatment in approximately 40% of cases where care was discontinued. The factors, used to predict which patients would have an unsuccessful vs successful outcome (defined as needing vs not requiring frequent care), were analyzed. A history of diet-pill use, purging, and exercise predicted an “unsuccessful outcome” (p = 0.02, p = 0.005, p=0.03, respectively). 32% of the 202 menarchal females lost their menses prior to treatment, and 54% had resumption of menses during treatment. Conclusions: Previous studies report high dropout rates in treatment of eating disorders across various treatment modalities and focus on those who remain in care. Here outcomes for all patients evaluated and treatment in an adolescent medicine care model are presented and show that a sizable portion, 37%, of those who drop out are recommended to stay in active treatment and only approximately 30% complete treatment. This finding supports an adolescent care model for eating disorder treatment and highlights that most adolescent patients go on to do well after leaving treatment, even if they left care earlier than recommended.